Heterosis studies for fruit yield and its attributing traits in Okra (Abelmoschus esculentus L. Moench) - Venkatesan, M; Priyadharshini, R; Anessa , R M S (Plant Science Today, 2025)
The experiment was aimed to identify superior cross combinations with desirable traits for the commercial use of F1 hybrids in okra, to achieve higher production and productivity. Eight parental lines and three testers of okra, along with their 24 F1 hybrids produced by a Line × Tester mating technique, were examined to analyze the magnitude of heterosis for eight quantitative characters. These hybrids and their eleven parents were evaluated during June 2022 using a Randomized Block Design (RBD) with three replicates at Plant Breeding Farm, Department of Genetics and Plant Breeding, Faculty of Agriculture, Annamalai University. Significant and desirable heterosis over the better-parent, mid-parent and standard checks was observed for all the characters examined. The maximum desirable heterosis was recorded in EC 305613 × Varsha Uphar, IC 22237 × Hissar Unnat and IC 22232 × Varsha Uphar over the relative heterosis, standard heterosis and heterobeltiosis for days to first flowering. The hybrids IC 18532 × Hissar Unnat, IC 22232 × Varsha Uphar, IC 22237 × Hissar Unnat, EC 305613 × Hissar Unnat, EC 305613 × Varsha Uphar, EC 305736 × Hissar Unnat and EC 305736 × Arka Abhay exhibited significantly high heterosis and high mean values for yield and most of the traits in desirable directions. Therefore, the cross combinations IC 18532 × Hissar Unnat, IC 22232 × Varsha Uphar and EC 305613 × Varsha Uphar offered excellent opportunities for the exploitation of hybrid vigour in okra. Hence, these crosses could have effectively used to develop high yielding hybrids with desirable traits in okra.